Retrocaval Ureter: Diagnostic Dilemma - A Case Report - Mughal, Rameez Ahmed; Qadeer, Zeeshan; Chughtai, Umer Javed; Khan, Faraz Basharat (Journal of Rawalpindi Medical College, 2026)
Retrocaval ureter is one of the unique and rarest congenital anomalies resulting from abnormal development of the inferior vena cava. The characteristic J-shaped or fishhook appearance is pathognomonic for this on CT urogram.1 Case presentation: A middle-aged man with a prolonged history of right lumbar pain spanning over three years presented to us. CT urogram depicted right moderate hydronephrosis with a fish-hook ureter. Subsequently, open surgical repair was performed successfully. At 6 months follow-up, he was pain-free with improvement in RFTs. In patients with progressive hydronephrosis or declining renal function, surgical repositioning of the ureter, either by open or laparoscopic method, is the treatment of choice. Keywords: Retrocaval ureter, congenital anomaly, inferior vena cava, hydronephrosis